1990
DOI: 10.1111/j.1476-5381.1990.tb15836.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of granisetron, ICS 205–930 and ondansetron on the visceral pain reflex induced by duodenal distension

Abstract: 1 Distension of the duodenum in anaesthetized rats, by rapid application of intraluminal pressures (10-75 cmH2O), evoked falls in diastolic blood pressure and intragastric pressure. 2 The distension-induced responses were blocked by pretreatment with morphine (20 mgkg ',s.c.), an action reversible by injection of naloxone (5 mg kg-1, i.v.). 3 Bilateral cervical vagotomy reduced the distension-evoked fall in intragastric pressure but had no effect on the corresponding fall in blood pressure. 4 Granisetron or IC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
38
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(45 citation statements)
references
References 20 publications
7
38
0
Order By: Relevance
“…77 Studies in animals suggest that 5-HT 3 receptors are putative excitatory mediators in visceral sensory pathways; thus, 5-HT 3 antagonists may reduce the level of perception to visceral distension. 88 However, the selective 5-HT 3 antagonists alosetron and ondansetron do not appear to have any significant effects on sensitivity to gastric distension in humans. 89,90 A recent study demonstrated reduction in dyspeptic symptoms in functional dyspepsia patients treated with alosetron.…”
Section: Antinociceptive Agentsmentioning
confidence: 99%
“…77 Studies in animals suggest that 5-HT 3 receptors are putative excitatory mediators in visceral sensory pathways; thus, 5-HT 3 antagonists may reduce the level of perception to visceral distension. 88 However, the selective 5-HT 3 antagonists alosetron and ondansetron do not appear to have any significant effects on sensitivity to gastric distension in humans. 89,90 A recent study demonstrated reduction in dyspeptic symptoms in functional dyspepsia patients treated with alosetron.…”
Section: Antinociceptive Agentsmentioning
confidence: 99%
“…Studies in the anaesthetized rat using acute levels of noxious colo-rectal or duodenal distension have demonstrated both pressor and depressor blood pressure pseudoaffective reflexes (Ness & Gebhart, 1988; Moss & Sanger, 1990). Of these cardiovascular pseudoaffective reflexes, the depressor response was found to be inhibited by the 5-HT3 receptor antagonists, granisetron and ondansetron, the latter showing only weak activity (Moss & Sanger, 1990;Banner & Sanger, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Of these cardiovascular pseudoaffective reflexes, the depressor response was found to be inhibited by the 5-HT3 receptor antagonists, granisetron and ondansetron, the latter showing only weak activity (Moss & Sanger, 1990;Banner & Sanger, 1991). As a consequence of these findings, granisetron was tested clinically as a potential visceral analgesic agent since pain and related gastrointestinal sensations are one of the diagnostic features of Irritable Bowel Syndrome (IBS; Thompson et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, there is a potential for 5-HT 3 receptors to modulate distension-induced postprandial changes in blood pressure. In rodents, the decreases in diastolic blood pressure resulting from duodenal distension with intraluminal pressures of 10 -75 cmH 2 O are attenuated by intravenous granisetron in doses of 1-100 g/kg (27).…”
Section: Discussionmentioning
confidence: 99%